Antibacterial Bioactivity Test of Bilimbi Fruit Ethanol Extract (Averrhoa bilimbi Linn). Against Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus - Anindita, Reza; Nathalia, Dede Dwi; Perwitasari, Melania; Putri, Intan Kurnia; Beandrade, Maya Uzia; Harahap, Nofria Rizki Amalia (Biology, Medicine, & Natural Product Chemistry, 2024)
One of the causes of acnes is the bacteria Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus. An alternative solution to this problem is to develop natural medicines from plants, one of which is the star fruit (Averrhoa bilimbi Linn). The purpose of this study was to test the bioactivity of star fruit against the growth of P. acnes, S. epidermidis, and S. aureus. This research method used an experimental research design with the treatment of A. bilimbi fruit ethanol extract concentrations of 50%, 60%, 70%, 80%, and 90%, chloramphenicol antibiotics as control (+), and sterile distilled water as control (-). All treatments were given to P. acnes, S. epidermidis, and S. aureus bacteria using the Kirby Baeur (disc diffusion) method. The results of this study were the effectiveness of the bioactivity compound of the ethanolic extract of A. bilimbi fruit seen on P. acnes and S. epidermidis bacteria with concentrations of 70%, 80%, and 90%. Thus, it can be concluded that A. bilimbi fruit has the potential to be developed as a natural medicine for acne caused by P. acnes and S. epidermidis.